2017
DOI: 10.17235/reed.2017.4569/2016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of screening on short-term outcome after surgery for colorectal cancer

Abstract: Aim: To investigate the influence of a screening program on the short-term outcome of patients undergoing surgery for colorectal cancer.Methods: Between April 2010 and December 2012 patients diagnosed with colorectal cancer via the screening program (n = 80) were compared with patients diagnosed elsewhere (n = 106). Only patients of ≥ 50 and ≤ 69 years of age diagnosed outside the program were selected as controls. The clinical variables included age, sex, American Society of Anesthesiologists (ASA) status, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…For example, lower uptake of bowel screening has been shown to be associated with younger age, male sex and socioeconomic deprivation [ 7 ]. In agreement with previous work [ 7 9 , 13 ], screen-detected patients in this study were more likely to be male, less likely to have rectal cancers and there was a non-significant trend towards lower socioeconomic deprivation. As would be expected, SD tumours were of a significantly lower UICC-TNM stage and there were a significantly lower number of emergency operations in this group.…”
Section: Discussionsupporting
confidence: 93%
“…For example, lower uptake of bowel screening has been shown to be associated with younger age, male sex and socioeconomic deprivation [ 7 ]. In agreement with previous work [ 7 9 , 13 ], screen-detected patients in this study were more likely to be male, less likely to have rectal cancers and there was a non-significant trend towards lower socioeconomic deprivation. As would be expected, SD tumours were of a significantly lower UICC-TNM stage and there were a significantly lower number of emergency operations in this group.…”
Section: Discussionsupporting
confidence: 93%
“…showed results that were in line with the results of Sebastian et al (1). We observed a significantly higher disease-free survival at five and ten years in patients diagnosed within the screening program (n = 200) as compared with those diagnosed following the appearance of symptoms (750).…”
supporting
confidence: 92%
“…We read the article "Lower morbidity and improved outcomes in patients with screen-detected colorectal cancer" and the accompanying editorial (1,2) with great interest. In this study, the authors reported that patients with colon cancer diagnosed as part of a screening program (n = 86) require fewer preoperative transfusions of blood products (3.5% vs 25%; p < 0.001) and also experience fewer overall postoperative complications than patients diagnosed outside such programs (n = 65) (35.4% vs 62.5%; p = 0.002).…”
mentioning
confidence: 99%
“…Although pathologic stage (TNM) and histologic parameters are the most important prognostic factors to determine long-term outcomes in CRC, there are other factors related to the host and surgical treatment which may have some bearing on our findings (14,15). Most authors agree that the subjects that voluntarily enroll in a screening program are more responsible, more health conscious, more likely to follow health care recommendations and usually have a better prognosis due to their habits and lifestyle.…”
Section: Discussionmentioning
confidence: 82%
“…However, a major limitation is its invasive nature, which is not always readily accepted by the general population (12,13). Several studies have reported differences in the histologic phenotype and survival in patients whose tumors were diagnosed via a screening program as opposed to those diagnosed as a result of clinical symptoms (10,(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%